Analysis of the Destabilization of Bacterial Membranes by Quaternary Ammonium Compounds: A Combined Experimental and Computational Study. (18th February 2020) - Alkhalifa, Saleh; Jennings, Megan C.; Granata, Daniele; Klein, Michael; Wuest, William M.; Minbiole, Kevin P. C.; Carnevale, Vincenzo
Abstract: The mechanism of action of quaternary ammonium compound (QAC) antiseptics has long been assumed to be straightforward membrane disruption, although the process of approaching and entering the membrane has little modeling precedent. Furthermore, questions have more recently arisen regarding bacterial resistance mechanisms, and why select classes of QACs (specifically, multicationic QACs) are less prone to resistance. In order to better understand such subtleties, a series of molecular dynamics simulations were utilized to help identify these molecular determinants, directly comparing mono‐, bis‐, and triscationic QACs in simulated membrane intercalation models. Three distinct membranes were simulated, mimicking the surfaces of Escherichia coli and Staphylococcus aureus, as well as a neutral phospholipid control. By analyzing the resulting trajectories in the form of a timeseries analysis, insight was gleaned regarding the significant steps and interactions involved in the destabilization of phospholipid bilayers within the bacterial membranes. Finally, to more specifically probe the effect of the hydrophobic section of the amphiphile that presumably penetrates the membrane, a series of alkyl‐ and ester‐based biscationic quaternary ammonium compounds were prepared, tested for antimicrobial activity against both Gram‐positive and Gram‐negative bacteria, and modeled. Abstract : The steps of QAC activity : Quaternary ammonium compounds (QACs) have long been assumed to disrupt bacterial membranes through electrostatic attraction followed by intercalation and subsequent disruption, but little modeling evidence has been presented to support this; the mechanism of action of multiQACs was even less clear. In a holistic study featuring computational modeling and SAR, we examine how QACs bearing multiple cations disrupt bacterial membranes.